FPGA Implementation of High Speed Hardware Efficient Carry Select Adder - Saravanakumar Saravanakumar; Vijeyakumar Vijeyakumar; Sakthisudhan Sakthisudhan (Institute of Advanced Engineering and Science, 2018)
This paper presents a novel architecture for high speed and hardware efficient carry select addition. We modify the two operand ripple carry addition followed in conventional Carry SeLect Adder(CSLA) with a simple and efficient gate level circuit to reduce area and delay significantly. For this, we use an increment 1 block for generating the sum outputs with carry input 1 instead of second pair ripple carry adder as in conventional CSLA. The novelty of the proposed approach is that it reduces area, and the delay due to carry propagation in second pair of adder cells. The proposed CSLA adder has been designed using structural VHDL code and synthesized using Altera Quartus II. Experimental results show that the proposed design outperform the previous approaches in terms of delay and area reduction.